Purine signaling pathway dysfunction in autism spectrum disorders: Evidence from multiple omics data - Dai, Si; Lin, Jingjing; Hou, Yanting; Luo, Xuerong; Shen, Yidong; Ou, Jianjun (Frontiers in Molecular Neuroscience, 2023)
Introduction Previous studies have suggested that the dysregulation of purine metabolism may be associated with autism spectrum disorder (ASD). Here, we adopted metabolomics and transcriptomics to verify and explore the underlying molecular mechanism of purine metabolism dysfunction in ASD and identify potential biomarkers within the purine metabolism pathway. Methods Ultra-high-performance liquid chromatography-mass spectrometry was used to obtain the plasma metabolic profiles of 12 patients with ASD and 12 typically developing (TD) children. RNA sequencing was used to screen differentially expressed genes related to the purine metabolic pathway and purine receptor-coding genes in 24 children with ASD and 21 healthy controls. Finally, serum uric acid levels were compared in 80 patients with ASD and 174 TD children to validate the omics results. Results A total of 66 identified metabolites showed significant between-group differences. Network analysis showed that purine metabolism was the most strongly enriched. Uric acid was one of the most highlighted nodes within the network. The transcriptomic study revealed significant differential expression of three purine metabolism-related genes (adenosine deaminase, adenylosuccinate lyase, and bifunctional enzyme neoformans 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) transformylase/inosine monophosphate (IMP) cyclohydrolase) (p < 0.01) and five purinergic receptor genes (P2X7, P2Y2, P2Y6, P2Y8, and P2Y10) (p < 0.05). In the validation sample, there was a significant difference in serum uric acid levels between the two groups (p < 0.001), and the area under the curve for uric acid was 0.812 (sensitivity, 82.5%; specificity, 63.8%). Discussion Patients with ASD had dysfunctional purine metabolic pathways, and blood uric acid may be a potential biomarker for ASD.